Geology, Structural Control and Hydrothermal Alteration of Porphyry Copper-Gold Deposits, Prospect Berambang, Sekotong District, West Lombok, West Nusa Tenggara, Indonesia - Faesal, Andi; Erintina, Melinda Dwi (Journal of Geoscience, Engineering, Environment, and Technology, 2025)
Berambang, located in the Sekotong district of West Lombok, West Nusa Tenggara, Indonesia, is part of the eastern Sunda Arc, known for world-class gold mines. The area, situated within a province rich in copper-gold deposits such as the Batu Hijau and Hu'u deposits, is still in the early stages of promising exploration. This study aims to identify and understand the geological factors controlling alteration and mineralization in the Berambang deposit, based on geomorphological, stratigraphic, and structural analyses, supported by fieldwork and laboratory investigations, including petrographic analysis and X-ray diffraction (XRD). The stratigraphy of Berambang is divided into four rock units: dacitic volcanic rock, diatreme breccia, diorite intrusion, and alluvium. Geomorphologically, Berambang consists of three landform units: intrusive hills, volcanic hills, and alluvial plains. Hydrothermal alteration in the area is categorized into four types: argillic alteration (kaolinite-illite-smectite), advanced argillic alteration (alunite-andalusite), propylitic alteration (chlorite-calcite-quartz-epidote), and potassic alteration (biotite-silica-magnetite). Notably, potassic alteration, an indicator of porphyry deposits, has been identified, with hydrothermal fluid activity being controlled by two fault systems in Berambang, trending northeast-southwest and northwest-southeast.